Digital technologies in medical insurance: development prospects during wartime - KRYSHTAL, Halyna; SKYBA, Hanna; KRYVOBERETS , Maryna (Ways to Improve Construction Efficiency, 2024)
The article examines the prospects for the development of digital technologies in the field of medical insurance in Ukraine under wartime conditions. The relevance of the study is determined by critical changes in the healthcare system during military actions, including a significant reduction in access to medical services, financial instability of insurance companies, and mass population displacement. The authors analyze key problems that have arisen in medical insurance during the war, such as the destruction of medical infrastructure, a decline in demand for voluntary insurance, increased risks for patients and insurers, insufficient digital integration, and fragmented regulatory frameworks. The study provides an overview of modern digital tools already applied in insurance and medical practices, including electronic policies, mobile applications, remote service systems, telemedicine services, and analytical dashboards for managing insurance portfolios. It has been established that existing digital solutions improve document management efficiency, accelerate claims processing, and ensure financial transparency. However, their integration remains incomplete, limiting the system’s potential to fully meet the needs of the population. Based on the conducted analysis, practical recommendations were formulated for the phased integration of digital solutions into the medical insurance system. These include the creation of a unified digital infrastructure for data exchange between insurers, medical institutions, and government bodies; the development of telemedicine and remote services; the implementation of artificial intelligence tools and big data analytics; the use of blockchain technologies to automate processes and increase transparency; and the improvement of the regulatory framework to ensure the legality and security of digital services. The results of the study indicate that digitalization of medical insurance is a key factor in enhancing system resilience, financial reliability, and readiness for post-war recovery. The implementation of these innovative solutions will contribute to the formation of a more accessible, transparent, and efficient healthcare system capable of providing social protection to the population even under crisis conditions.